2020
DOI: 10.1177/0959683620913920
|View full text |Cite
|
Sign up to set email alerts
|

Late-Holocene vegetation dynamics and disturbance regimes in north Patagonia Argentina (40°S)

Abstract: Natural disturbance processes such as volcanic eruptions, fire and human activities are important vegetation drivers in north Patagonia. Here, we tested the impact of volcanic ash fall and fire on vegetation composition analysing two sediment records, Lake Avutarda and Lake Bruja, located in the forest-steppe transition at 40°S. In addition, our analysis provides the first account on the history of Nothofagus alpina at its eastern distribution limits. Our results comprise the last 3000 years, indicating the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…In palynological records, the abundance of N. dombeyi type is always variable, and few studies have assessed directly the responses to volcanic events. Álvarez‐Barra et al ( 2020 ) demonstrated that well‐developed forests were not affected in the long term by tephra fall smaller than 20 cm. However, after the large eruption of So‐A, the pollen abundance of N. dombeyi ‐type was strongly affected (this study and Dickson et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In palynological records, the abundance of N. dombeyi type is always variable, and few studies have assessed directly the responses to volcanic events. Álvarez‐Barra et al ( 2020 ) demonstrated that well‐developed forests were not affected in the long term by tephra fall smaller than 20 cm. However, after the large eruption of So‐A, the pollen abundance of N. dombeyi ‐type was strongly affected (this study and Dickson et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, Jara and Moreno (2012) associate major increases in Eucryphia/ Caldcluvia trees with tephra fall (Lake Pichilafqu en, 41 S). In contrast, Jara et al (2019) document that changes in the Southern Westerlies (SW) were the dominant driver of vegetation change rather than disturbance (Lago Espejo, 43 S) Studies on the impact of ash deposition on vegetation have been conducted also east of the main mountain chain ( Alvarez-Barra et al, 2020;Moreno-Gonz alez, 2020), showing negligible impact of ash deposition on the vegetation composition.…”
Section: Introductionmentioning
confidence: 99%
“…Studies also examined the spatial growth patterns (Donoso, 1988;Donoso et al, 1993;Echeverría and Lara, 2004;Puntieri et al, 2006;Sabatier et al, 2011) and site index models to quantify the productivity of a determined area with silvicultural purposes (Attis et al, 2015;Trincado et al, 2002). Unfortunately, few palynological records show the Nothofagus obliqua pollen type, which comprises pollen grains from N. obliqua and N. alpina ( Alvarez-Barra et al, 2020;Markgraf et al, 2009;Nanavati et al, 2020), and yet, little is reported on their Holocene history within their distribution range in northern Patagonian Argentina.…”
Section: Introductionmentioning
confidence: 99%